2013
DOI: 10.1074/jbc.m113.496414
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-biased Trafficking of Somatostatin Receptor 2A in Enteric Neurons

Abstract: Background: Somatostatin regulates gut function via neuronal somatostatin receptors. Results: Somatostatin susceptibility to degradation by endosomal endothelin-converting enzyme 1 (ECE-1) defines receptor function. Conclusion: ECE-1 regulates the duration of somatostatin receptor signaling and trafficking. Significance: Therapeutic somatostatin analogs are ECE-1-resistant, which underlies their prolonged actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 32 publications
3
33
0
Order By: Relevance
“…SP stimulated interactions between the NK 1 R and ECE-1c and ECE-1d, which constitutively internalize in the same endosomes as GPCRs (22). ECE-1 similarly interacts with somatostatin 2A receptors (15). Whether such interactions enhance neuropeptide degradation remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SP stimulated interactions between the NK 1 R and ECE-1c and ECE-1d, which constitutively internalize in the same endosomes as GPCRs (22). ECE-1 similarly interacts with somatostatin 2A receptors (15). Whether such interactions enhance neuropeptide degradation remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Products were digested with BamHI and XhoI and ligated into pcDNA3-RLuc8 using the BamHI and XhoI sites. The bioluminescence resonance energy transfer (BRET) sensors (human) NK 1 R-RLuc8, ␤ARR1-YFP, ␤ARR2-YFP, ECE1a-d-YFP, KRas-Venus, Rab5a-Venus, and Rab11-Venus were generated as described previously (9,14,15). The FRET sensors CytoEKAR and NucEKAR (16) were from Addgene (Cambridge, MA) (plasmids 18680 and 18681, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Although not specifically examined, it is possible that the differences in MOR recycling may be related to susceptibility to degradation by endosomal peptidases, as demonstrated for ECE-2 (21). Previous studies have demonstrated that ECE-1 is a major determinant of receptor recycling and signaling in myenteric neurons (44,71). The retention of MOR following treatment with the nonpeptide MOR agonist loperamide, which is unlikely to be endopeptidase substrate, suggests that other mechanisms are likely to be involved.…”
Section: G260mentioning
confidence: 99%
“…Receptor endocytosis can also influence the type and duration of subsequent cellular signaling in response to MOR agonists (23). We examined ligand-induced MOR endocytosis and recycling in myenteric neurons using organotypic wholemount preparations as described previously (44,48,71). Under basal conditions, MOR-IR was localized to the cell surface of the soma and neurites of untreated neurons, with a lower proportion of total surface MOR-IR relative to other GPCRs examined in enteric neurons (NK 1 R, DOR, or SSTR 2A :…”
Section: Mor Is Expressed By Enteric Neurons Throughout the Gastrointmentioning
confidence: 99%
See 1 more Smart Citation